Multifaceted Role of Sialylation in Prion Diseases - Baskakov, Ilia V.; Katorcha, Elizaveta (Frontiers in Neuroscience, 2016)
Mammalian prion or PrPSc is a proteinaceous infectious agent that consists of a misfolded, self-replicating state of a sialoglycoprotein called the prion protein or PrPC. Sialylation of the prion protein N-linked glycans was discovered more than 30 years ago, yet the role of sialylation in prion pathogenesis remains poorly understood. Recent years have witnessed extraordinary growth in interest in sialylation and established a critical role for sialic acids in host invasion and host-pathogen interactions. This review article summarizes current knowledge on the role of sialylation of the prion protein in prion diseases. First, we discuss the correlation between sialylation of PrPSc glycans and prion infectivity and describe the factors that control sialylation of PrPSc. Second, we explain how glycan sialylation contributes to the prion replication barrier, defines strain-specific glycoform ratios and imposes constraints for PrPSc structure. Third, several topics, including a possible role for sialylation in animal-to-human prion transmission, prion lymphotropism, toxicity, strain interference and normal function of PrPC, are critically reviewed. Finally, a metabolic hypothesis on the role of sialylation in the etiology of sporadic prion diseases is proposed.